STUDY OF METALLO BETA LACTAMASE (MBL) PRODUCING Pseudomonas aeruginosa SENSITIVITY ON TETRACYCLINE GROUP ANTIBIOTIC IN CLINICAL ISOLATE COLLECTIONS OF DEPARTMENT OF MICROBIOLOGY FACULTY OF MEDICINE UNIVERSITAS GADJAH MADA FROM 2011-2013 - , YUNITA HARISA PUTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : One of the most common pathogen that can cause nosocomial and opportunistic infection is Pseudomonas aeruginosa. This gram-negative bacteria is frequently resistant to some antibiotics due to production of MBL. To avoid unnecessary prescription, it is essential to know the correct antibiotic. Objective : The objective of this study is to know the sensitivity of metallo beta lactamase producing Pseudomonas aeruginosa on Tetracycline group antibiotic and to know the proportion of metallo beta lactamase producing Pseudomonas aeruginosa in clinical isolate collections of Department of Microbiology Faculty of Medicine Universitas Gadjah Mada from 2011-2013. Method : The design of the study is descriptive study. The samples are clinical isolates obtained from Department of Microbiology Faculty of Medicine Universitas Gadjah Mada. The sample size estimated is 25 clinical isolates. Results : 3 (12%) out of 25 were MBL producing Pseudomonas aeruginosa. 22 (88%) were non-MBL. 3(100%) of MBL positive were resistant to tetracycline. Conclusion : MBL positive P.aeruginosa totally resistant to tetracycline. The MBL positive one have low susceptibility towards tetracycline.